Dampak Sistem Penghawaan dan Pencahayaan terhadap Sick Building Syndrome - Daryanto Daryanto (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Activities of office workers are most spent indoors. Unwittingly office buildings and enclosed spaces with air conditioning system usually do not have good ventilation and allow natural lighting. This condition may cause sick building syndrome (SBS). It is a collection health issues arising in relation to the time spent in a building and the air quality. A study was conducted through a literature review and field observations to obtain the impacts of SBS, as well as the prevention and solution of architectural aspects. From the results of the study, it was obtained that printer, computer, cigarette smoke, building materials, etc., gave rise to free radicals. Theair polluted by free radicals may cause medical problems such as headaches, eye irritation, quickly tired and weary body, runny nose, itchy throat, difficulty in concentrating, dry skin and dry cough. This research is expected to improve the quality of life of workers that can be started from the improved quality of health.